Legislators do not harness voter support for disaster preparedness. Issue 1 (11th October 2022) - Anderson, Sarah E.; DeLeo, Rob; Taylor, Kristin
Abstract: Natural disasters are worsening, but elected officials have not adequately invested in programs that would improve disaster preparedness. Federal spending and election outcomes have been taken to suggest policymakers' failure to support long‐term preparedness results from a lack of interest in disaster preparedness among voters and a pervasive preference among voters for more spending on disaster relief than preparedness. However, our national survey experiment on state legislators and public preferences shows that the public is equally interested in disaster preparedness and relief and that both the public and legislators are open to increases in spending on preparedness. The support for preparedness can be motivated by information about past disaster losses rather than having to make difficult predictions about future losses. This study suggests the lack of preparedness spending stems not from voter disinterest, but from a failure of legislators to harness voter support for preparedness. Specifically, the legislators included in our study report being less responsive to attentive voters' preferences on preparedness than relief. 摘要: 自然灾害正在恶化，但获选官员还未充分投入于一系列改善灾害预备的计划。联邦开支和选举结果表明，政策制定者未能支持长期备灾的原因是因为选民对备灾缺乏兴趣，以及选民普遍倾向于在救灾方面的支出多于备灾。不过，我们对州立法者和公众偏好进行的全国调查实验表明，公众对备灾和救灾同样感兴趣，并且公众和立法者都对增加备灾支出一事持开放态度。激发备灾支持一事能通过关于过去灾害损失的信息来完成，而不是必须对未来灾害损失作出艰难的预测。本研究表明，备灾支出不足并非源于选民的不感兴趣，而是立法者未能充分利用选民对备灾的支持。具体而言，本研究中的立法者报告，其对选民备灾偏好的响应度低于选民救灾偏好。 Resumen: Los desastres naturales están empeorando, pero los funcionarios electos no han invertido adecuadamente en programas que mejorarían la preparación para desastres. Se ha considerado que el gasto federal y los resultados de las elecciones sugieren que el hecho de que los legisladores no respalden la preparación a largo plazo se debe a la falta de interés en la preparación para desastres entre los votantes y una preferencia generalizada entre los votantes por gastar más en ayuda para desastres que en preparación. Sin embargo, nuestro experimento de encuesta nacional sobre las preferencias del público y los legisladores estatales muestra que el público está igualmente interesado en la preparación y el socorro en casos de desastre y que tanto el público como los legisladores están abiertos a aumentar el gasto en preparación. El apoyo para la preparación se puede motivar con información sobre pérdidas por desastres pasadas en lugar de tener que hacer predicciones difíciles sobre pérdidas futuras. Este estudio sugiere que la falta de gasto en preparación no se debe al desinterés de los votantes, sino a que los legisladores no lograron aprovechar el apoyo de los votantes para la preparación. Específicamente, los legisladores incluidos en nuestro estudio informan que responden menos a las preferencias de preparación de los votantes atentos que al alivio.